The impacts of performance relative to analyst forecasts and analyst coverage on firm R&D intensity - Gentry, Richard J; Shen, Wei (Strategic Management Journal, 2013)
Abstract Taking an agency theory perspective of managers as risk averse and self‐interest seeking and focusing on externally generated analyst forecasts as the performance target, we propose that managers tend to cut R&D expenses when they are under pressure to meet analyst forecasts, especially when they face an increase in employment risk after missing the forecasts. We further argue that analyst coverage can serve as an external monitoring mechanism to help contain this agency problem. We test these arguments with data from a sample of U.S. manufacturing firms during the period of 1979 to 2005. Copyright © 2012 John Wiley & Sons, Ltd.